2008
DOI: 10.1021/ja8001259
|View full text |Cite
|
Sign up to set email alerts
|

Complete Supramolecular Self-Assembled Adlayer on a Silicon Surface at Room Temperature

Abstract: The engineering of a complete adlayer of organic nanolines by supramolecular self-assembly has been achieved for the first time on a silicon-based surface at room temperature and has been studied by scanning tunneling microscopy. This complete adlayer has been successfully obtained thanks to the combination of a specific Si(111)-B square root 3x square root 3R30 degrees semiconductive surface and of strong hydrogen bonds between a pair of dipolar molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…Our work in this domain illustrates well the effect of temperature in self-assembly formation [22][23][24]. Although molecular deposition Reprinted with permission from [19] was performed at room temperature, this thermal energy was sufficient for molecules to overcome diffusion barriers and then form different self-assemblies.…”
Section: Heatmentioning
confidence: 52%
See 1 more Smart Citation
“…Our work in this domain illustrates well the effect of temperature in self-assembly formation [22][23][24]. Although molecular deposition Reprinted with permission from [19] was performed at room temperature, this thermal energy was sufficient for molecules to overcome diffusion barriers and then form different self-assemblies.…”
Section: Heatmentioning
confidence: 52%
“…Recently, we have demonstrated that the molecule-surface interactions can be controlled by using the Si(111)-B-(√3 × √3)-R30°surface, noted Si(111)-B. The silicon adatoms dangling bonds are depopulated because of the presence of a boron atom underneath each silicon adatom, leading to a weak π-conjugated moleculesurface interaction [22,24,[50][51][52]. In all these cases, molecule-surface interaction is weak enough to achieve the formation of large-scale supramolecular networks.…”
Section: Adsorption Of Bistable Azobenzene Molecules On Semiconductorsmentioning
confidence: 99%
“…4 Multicomponent self-assembled networks on highly ordered pyrolytic graphite (HOPG) or metallic surfaces have been much investigated, 5−13 but equivalent supramolecular structures have been rarely observed on silicon-based substrates 14,15 mostly due to their propensity to form covalent bonds. The fundamental understanding of chemical interactions occurring between a selfassembly arrangement and a semiconductor surface consists of two complex parts where molecule−substrate and molecule− molecule interactions compete.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, only few works are devoted to the 2D molecular adsorption on semiconductor substrates, and particularly on silicon surfaces due to the high reactivity of the silicon dangling bonds [4]. To avoid the formation of covalent bonding between molecules and the Si substrate, two strategies can be envisioned either by choosing an appropriate molecular architecture, or thanks to passivation of the Si surface dangling bonds [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%